HUBUNGAN POSISI MENYUSUI DENGAN TERJADINYA BENDUNGAN ASI PADA IBU MENYUSUI - Juni Andri Kariny, Elsy; Rahayu, Esti; Purwanggi, Annisa (Jurnal Kesehatan, 2023)
Background: Breast milk dams are caused when breast milk is not immediately released which causesblockages in the venous and lymphatic flow so that breast milk collects in the lactive duct systemwhich causes swelling. Milk dams mostly occur in the second to the tenth postpartum period. InIndonesia in 2016 mothers who experienced breast milk were (71.1%) with the highest rate inIndonesia (37.1%) (Ministry of Health RI, 2016). Research objective: To determine the relationshipbetween breastfeeding position and the occurrence of breast milk retention in breastfeeding mothersat BPS Sri Kadarwati. Research method: Quantitative research design with a cross-sectionalapproach using secondary data. The population in this study were breastfeeding mothers and asample of 35 respondents was obtained. Data analysis using univariate and bivariate analysis.Research results: In the research diary, it was found that some respondents experienced breast milkdams, namely 22 (62.9%) and there were 19 (54.3%) respondents who experienced an incorrectbreastfeeding position. There is a relationship between the position of breastfeeding and theoccurrence of ASI dams, namely the value (p value = 0.012).